Micro Analysis of Selected Transition Metals Using Carrier Precipitation and Speciation of Chromium - Mehra, M.C.; Guimond, A.S. (Asian Journal of Chemistry, 2010)
A study was undertaken for successive analysis of micro amounts of transition metals in aqueous samples. Amongst the four carriers examined, Y(OH)3 has been found to be an efficient carrier for quantitative separation and preconcentration of elements in μg and sub μg range. The analytical scheme is simple to adapt and requires minimal experimental set up. In addition, Cr(III) and Cr(VI) in aqueous samples can be determined through direct carrier precipitation and reductive coprecipitation with the carrier ions.